Relationship between Chemical Structures and Biological Activities of Triterpenoid Saponins from Soybean - Yumiko Yoshiki; Sigemitsu KUDOU; Kazuyoshi Ōkubo (1998)
Saponins can be found in more than one hundred plant families and in some marine animals. However, chemical investigation of soybean (Glycine max L. Merrill) saponins has begun only as recently as the 1970s. Here we focus on the chemical structure, the content, and biological activity of soybean saponins in current studies. Especially, we focus on 2,3-dihydro-2,5-dihydroxy-6-methyl-4H-pyran-4-one (DDMP) conjugated saponins and define the chemical structure of this as a natural precursor of group B and E saponins.